Prevention of Child Marriage Age in the Perspective of Human Rights - Rudyanti Dorotea Tobing (Faculty of Law, Sriwijaya University, Indonesia, 2018)
One of the rights guaranteed by the 1945 Constitution of the Republic of Indonesia is the right to marry and have children. Marriage is the beginning of the process of embodiment of the formation of a family in human life. Therefore, marriage is not merely the fulfillment of biological needs, but more than that. Marriage is a part of Human Rights stipulated in Article 10 of the Human Rights Law that everyone shall have the right to start a family and to continue the offspring through legitimate marriage and it may only take place at the free will of the prospective husband and future wife. Marriage is the inner bond between a man and a woman as a husband and wife with the aim of forming a happy and eternal family (household) based on the One Supreme God (Article 1 of the Marriage Law). Based on the article, it can be seen that the purpose of marriage is to establish a happiness and an eternal household based on the One God. Marriage is permissible for those who have met the age limit for marriage as set forth in Article 7(1) of the Marriage Law, for man nineteeen years old and for woman sixteen years old, but in fact under age marriages still happen. According to human rights perspective, under age marriage is the action of grabbing children freedom, namely the right to grow and develop optimally. Prevention of under age marriage, should be done so the children still get their basic rights.